A NECESSIDADE DA AMPLIAÇÃO DO ALFABETISMO CRÍTICO POR MEIO DO DESENVOLVIMENTO DA CAPACIDADE LEITORA - Roger Cazotto Terra, Kenner; Crispim França Luquetti, Eliana; Maria da Fonseca Souza, Sonia; Sanches Fófano, Clodoaldo (LINKSCIENCEPLACE, 2026)
This study aims to present a possible dialogue between the studies of the Language of Art and Analysis of French Speech Discourse (AFSD). It has discussed the need for an education that enhances critical literacy in relation to the media and gives importance to the development of skills that will assist the progress of cognitive skills in learners. Among those skills that need to be expanded in the learner, it is worth mentioning the practice of reading that produces a subject /reader who is an active part in the discursive construction. Thus, the text is not a finished structure, the meaning of the text is complete in its reader and reading is a participatory, active, interactive action. In this way, the learner will have the capacity to react critically against the seductions of advertising texts, not behaving as a passive person, becoming an autonomous citizen, free, complete, and ready to exercise citizenship as an instrument transforming the environment in which he does part.